Competitive Intelligence and Product Development/Innovations in Pharmaceutical Firms in Lagos State, Nigeria - Nduka Kenneth Omede; Amaechi Sylvester Egwuenu; Ezem Matthew Ibekwe (Universitas Jember, 2020)
This study examined competitive intelligence and product development and innovation in pharmaceutical firms in Lagos State, Nigeria. Three hypotheses were formulated to determine whether or not a relationship exist between competitive intelligence and product development and innovation in pharmaceutical firms in Lagos State, Nigeria. The study adopted a survey research design to obtain data, using a structured questionnaire which was analyzed using Pearson’s product moment coefficient of correlation. The result indicated that there exists a significant relationship between competitive intelligence and product development and innovation in pharmaceutical firms in Lagos State, Nigeria. Based on the finding it was concluded that the process of product development and innovation cannot be successful except there is information about customer’s needs, wants and expectations of which the innovation products or services intends to serve. The study recommended among others that pharmaceutical firms should leverage on information gathering and sharing to determine the nature of the new product and service so that the new product offerings will be more valued and satisfying than the existing ones that are offered by the competitors. Keywords: Competitive Intelligence, Information gathering and sharing, Product Development and innovations, New products, New product offerings, Pharmaceutical firms.